O.8.1Aboriginal interpreters improve hospitalised patient experience in northern Australia: Presenter(s): Vicki Kerrigan, Charles Darwin University, Australia; Stuart Yiwarr McGrath, Charles Darwin University, Australia. (April 2023) - Ralph, Anna; Hefler, Marita
Abstract : Background: In hospitals globally, interpreters are underused. Low uptake of interpreters is commonly attributed to limited interpreter availability, time constraints and that interpreter-mediated communication in healthcare is an aberration. In Australia's north at Royal Darwin Hospital (RDH), it is estimated around 50% of Aboriginal patients would benefit from an interpreter, yet approximately 17% get access. Recognising this contributes to a culturally unsafe system, a new model of Aboriginal interpreter use in which interpreters were embedded in a renal medical team for 4 weeks in 2019 was piloted. Methods: This pilot was part of a larger Participatory Action Research study examining strategies to achieve culturally safe communication at RDH. Two Yol?u and two Tiwi language interpreters were embedded in a medical team. Data sources included interviews with doctors, interpreters, and an interpreter trainer; doctors reflective journals; and field notes. Aligning with PAR's transformative goals a critical theory lens guided analysis. Findings: Whilst English is the operational language of the hospital, it is not the language most spoken by renal patients. Almost 90% of patients were Aboriginal and nearly 80% spoke one or more of the 15 languages identified in the unit. The power imbalance between Aboriginal language speaking patients and English-speaking providers was equalised through the presence of interpreters. Patients described feeling "stuck" and disempowered when forced to communicate in English. After receiving access to trusted interpreters' patients reported feeling "satisfied" with their care and empowered. Discussion: By embedding Aboriginal language interpreters in the medical team, the power dynamics between doctors and Aboriginal clients shifted towards cultural safety. A culturally unsafe system which diminished and neglected patients' needs was overturned by a small but significant system change. Scale up of learnings from this pilot to broader implementation in the health service is the current focus of ongoing implementation research.